Do Voters Reward Economic Performance? Evidence from Indonesia Local Elections - Agusto Agusto; Ni Made Sukartini (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study investigates whether regional economic performance influences electoral margins in local elections in Indonesia. Drawing on Economic Voting Theory, the study examines the effects of economic growth, poverty, and income inequality on candidate margins of victory while controlling for incumbency and political party affiliation. Using panel data from 508 districts and municipalities for 2017–2024, the study employs a fixed-effects model with cluster-robust standard errors and robustness checks using lagged economic indicators. The results provide limited evidence supporting Economic Voting Theory. Economic growth, poverty, and income inequality do not significantly influence electoral margins. Further robustness analysis confirms that lagged economic conditions also fail to explain electoral outcomes. Conversely, incumbency has a strong positive effect on margins of victory, indicating a substantial incumbency advantage in local elections in Indonesia. Political party affiliation also has a positive effect on electoral performance, albeit with weaker statistical significance. These findings suggest that local election competition in Indonesia is driven more by political factors than by retrospective evaluations of economic performance. This study contributes to the literature by highlighting the contextual limitations of Economic Voting Theory in decentralized democracies and developing countries.